ANALISIS SEDIMENTOLOGI BATUPASIR FORMASI LATIH BERDASARKAN DATA PERMUKAAN DI DAERAH BERAU, KALIMANTAN TIMUR - , WINDA KURNIAWATI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Latih Formation in Berau area mainly composed of sandstone, which in Tarakan Sub-basin known as Meliat Formation, is believed as a proven reservoir. In Berau area, which is still part of Berau Sub-basin of Tarakan Basin, Latih Formation are found in Tanjung Redeb area. A comprehensive knowledge in characteristic and sedimentology of Latih Formation is expected to also be applied on Meliat Formation as well, thus leads to a more focused exploration activity. In order to reach the aim, two traverse lines along the road of Tanjung Redeb-Sangatta and Tanjung Redeb-Tepian have been measured and analyzed to identify the lower part vertical succession, with total 190meters thick, of Latih Formation. Laboratorium analysis includes petrographical (13 samples), granulometry (6 samples) and paleontological analyses (3 samples). A dominant composition of arenites with iron oxide of hematit as cement is identified from sandstone samples under petrographical analysis. Based on granulometry analysis, sandstone samples has average grain size of medium sand, poorly sorted, sub-rounded morphology and very equant sphericity. Paleontological analysis has mentioned that Latih Formation was deposited within mid-neritic to transitional paleobathymetry during Middle Miocene (N8-N10). Typical of deltaic depositional environment, with combination of wave and tidal influence, is mainly identified on the lower part of Latih Formation.